Thermal transport in bismuth telluride quintuple layer: mode-resolved phonon properties and substrate effects - Shao, Cheng (Sci Rep, 2016)
The successful exfoliation of atomically-thin bismuth telluride (Bi(2)Te(3)) quintuple layer (QL) attracts tremendous research interest in this strongly anharmonic quasi-two-dimensional material. The thermal transport properties of this material are not well understood, especially the mode-wise properties and when it is coupled with a substrate. In this work, we have performed molecular dynamics simulations and normal mode analysis to study the mode-resolved thermal transport in freestanding and supported Bi(2)Te(3) QL. The detailed mode-wise phonon properties are calculated and the accumulated thermal conductivities with respect to phonon mean free path (MFP) are constructed. It is shown that 60% of the thermal transport is contributed by phonons with MFP longer than 20 nm. Coupling with a-SiO(2) substrate leads to about 60% reduction of thermal conductivity. Through varying the interfacial coupling strength and the atomic mass of substrate, we also find that phonon in Bi(2)Te(3) QL is more strongly scattered by interfacial potential and its transport process is less affected by the dynamics of substrate. Our study provides an in-depth understanding of heat transport in Bi(2)Te(3) QL and is helpful in further tailoring its thermal property through nanostructuring.